Chronischer Pruritus - Kremer, Andreas (Medizinische Monatsschrift für Pharmazeuten, 2019)
Chronic pruritus is an agonizing Symptom accompanying various diseases which often represents an interdisciplinary diagnostic and therapeutic challenge. Approxi-mately 15 % of the population suffers from this symptom. Aside general measures such as a cold surrounding and topical treatment, several systemic therapies such as anticonvulsives and antidepressants may be used in different pruritus-associated diseases due to similar chronification mechanisms. Novel insights into the neuro-biological mechanisms of chronic pruritus have led to new therapeutic approaches. Still we are currently far away from an optimal care of patients suffering from chronic pruritus.
CRIS-Team Scopus Importer:2021-04-20